2023
DOI: 10.3390/plants12142592
|View full text |Cite
|
Sign up to set email alerts
|

Response of Maize Seedlings to Silicon Dioxide Nanoparticles (SiO2NPs) under Drought Stress

Abstract: Recently, the use of nanofertilizers has received a great deal of attention in managing plants under biotic and abiotic stresses. However, studies that elucidate the role of silicon dioxide nanoparticles (SiO2NPs) in regulating maize tolerance to drought stress are still at early stages of development. In this study, plants that were treated with SiO2NPs (0.25 g/L as foliar spray) displayed considerable improvement in the growth indices, despite being subjected to drought stress. In addition, the action of SiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…In the study, it was reported that drought stress caused a significant decrease in chlorophyll, fresh/dry weight, and biomass, but NaSiO2 application improved the leaf area index (LAI), chlorophyll, and biomass under severe water deficiency. Sharf-Eldin et al investigated the response of corn seedlings to NaSiO 2 application under drought stress and reported that 0.25 g L −1 foliar application of NaSiO 2 provided a significant improvement in the growth index of corn plants exposed to drought stress [45]. Researchers also declared that these particles caused a significant increase in chlorophyll, proline, cell membrane integrity, leaf water content, SOD, CAT, and guaiacol peroxidase (G-POX) levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, it was reported that drought stress caused a significant decrease in chlorophyll, fresh/dry weight, and biomass, but NaSiO2 application improved the leaf area index (LAI), chlorophyll, and biomass under severe water deficiency. Sharf-Eldin et al investigated the response of corn seedlings to NaSiO 2 application under drought stress and reported that 0.25 g L −1 foliar application of NaSiO 2 provided a significant improvement in the growth index of corn plants exposed to drought stress [45]. Researchers also declared that these particles caused a significant increase in chlorophyll, proline, cell membrane integrity, leaf water content, SOD, CAT, and guaiacol peroxidase (G-POX) levels.…”
Section: Introductionmentioning
confidence: 99%
“…According to Al-Mokadem et al (2023), foliar application of 3 mM SiNPs significantly increased activities of antioxidant enzymes like CAT, SOD, POX, GR, and APX of Zea mays under water deficit conditions. Similarly, the application of SiNPs increased the activities of CAT, SOD, or G-POX, except for APX, of maize plants subjected to DS (Figure 2) (Sharf-Eldin et al, 2023).…”
Section: Sinps Improve the Antioxidant Defence Systemmentioning
confidence: 83%
“…The absorption and accumulation of NPs can vary among different plant species, depending on their uptake mechanisms, physical characteristics, transport, and distribution in specific plant parts which may trigger defence mechanisms in response to NPs (Verma et al, 2022). Si may be administered either directly to the root system as basal dressing (Fetsiukh et al, 2021), or as foliar spray onto plant's leaves (Sharf-Eldin et al, 2023). The foliar spray can penetrate leaves and then be transported to various plant organs through cuticular layer or stomata (Hellala et al, 2020).…”
Section: Uptake and Transport Of Sinpsmentioning
confidence: 99%
See 2 more Smart Citations